2019
DOI: 10.1016/j.vas.2019.100062
|View full text |Cite
|
Sign up to set email alerts
|

Intra-lingual suture pattern for prevention of self-suckling in cows

Abstract: Highlights Less invasive technique through small mucosal incisions. Overcomes the disadvantages of the traditional procedures. Minimal lingual histopathological changes. No serious complications were reported. Self-sucking was abolished and animal behavior changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…El-Sherif and Seddek et al [12,13] performed lessinvasive surgical methods by applying silk stitches to the tissues of the tongue to make the tongue's dorsal surface convex to prevent this abnormal behavior. These techniques had a low success rate in the long term because the amount of tongue tissue involved in the stitches was less than the minimum amount required to make a change in the tongue contour, so the animals could theoretically continue sucking after surgery [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El-Sherif and Seddek et al [12,13] performed lessinvasive surgical methods by applying silk stitches to the tissues of the tongue to make the tongue's dorsal surface convex to prevent this abnormal behavior. These techniques had a low success rate in the long term because the amount of tongue tissue involved in the stitches was less than the minimum amount required to make a change in the tongue contour, so the animals could theoretically continue sucking after surgery [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A six-month follow-up observation revealed that self-sucking had completely disappeared in all of the treated animals. In the previous studies, the animals' trials of self-sucking lasted 3 weeks in the intra-lingual suture pattern technique [13] and more than 4 weeks were needed for complete healing in glossectomy techniques [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El-Sherif and Seddek et al [12,13] performed less-invasive surgical methods by applying silk stitches to the tissues of the tongue to make the tongue's dorsal surface convex to prevent this abnormal behavior. These techniques had a low success rate in the long term because the amount of tongue tissue involved in the stitches was less than the minimum amount required to make a change in the tongue contour, so the animals could theoretically continue sucking after surgery [8-10].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques were designed to prevent animals from being able to cup the dorsum of their tongues and suck teats, including the ventral glossectomy technique [7][8][9][10] and the lateral glossectomy technique [11,10]. Recently, two less-invasive techniques were performed by applying silk stitches to the free portion of the tongue [12,13]. However, these techniques varied in their complications and success rates.…”
Section: Introductionmentioning
confidence: 99%